What Makes People Reoffend? Predictors of Reconviction – A 2-year Longitudinal Study. Issue 5 (4th May 2023) - Friedrich, Wiola
ABSTRACT: Male offenders constitute a substantial proportion of the whole male prison population. A comparison of recidivism rates in the entire world shows that the return to criminal behavior ranges from 9% to even 79%. Recent studies indicate that a risk for criminal reoffending is based on many different factors. The aim of the study was to determine the influence of personality, criminal thinking styles, stress coping styles, moral feelings, some aspects of socialization and crime characteristics on reoffending. This longitudinal study was conducted twice over the course of two years and involved 247 male prison inmates housed in 20 Polish prisons. Recidivism and other penitentiary data were obtained from administrative records. Independent sample t-tests were used to indicate differences between recidivists and non-recidivists. Logistic multiple linear regression analyses were used to test the potential predictive value of the potential risk factors for recidivism. The overall recidivism rate was 35%. The study findings showed that sentimentality, shame, the type of the correctional facility, the criminal record, and the type of the inmate's upbringing had an impact on recidivism while therapeutic methods and a sense of contrition could decrease the probability of reoffending.